2006
DOI: 10.1161/01.res.0000238360.33284.a0
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Pools of Mesenchyme Contribute to the Development of the Atrial Septum

Abstract: Closure of the primary atrial foramen is achieved by fusion of the atrioventricular cushions with the mesenchymal cap on the leading edge of the muscular primary atrial septum. A fourth component involved is the vestibular spine, originally described by His in 1880 as an intra-cardiac continuation of the extra-cardiac mesenchyme of the dorsal mesocardium. The morphogenesis of this area is of great clinical interest, because of the high incidence of atrial and atrioventricular septal defects. Nonetheless, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 24 publications
5
57
0
2
Order By: Relevance
“…This fact had also not escaped us when we supported, in a series of investigations, the notion that the pulmonary vein did not originate from the systemic venous sinus (Webb et al, 1998a(Webb et al, ,b, 2000(Webb et al, , 2001Soufan et al, 2004;Christoffels et al, 2006). Throughout our studies, the key point of our own argumentation has been that, in terms of morphology, the systemic venous sinus cannot be distinguished as a morphologic entity separate from the remainder of the atrial chambers until after the formation of the so-called venous valves (Anderson et al, 2006). In our opinion, Manner and Merkel (2007) fail to give sufficient emphasis to the investigations, already mentioned above, in which we showed that, at the stages before the systemic venous sinus could be distinguished, and before the appearance of the pulmonary vein, the systemic venous tributaries still are embedded in the mesenchyme of the septum transversum, and not yet incorporated into the pericardial cavity (Soufan et al, 2004;Christoffels et al, 2006).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…This fact had also not escaped us when we supported, in a series of investigations, the notion that the pulmonary vein did not originate from the systemic venous sinus (Webb et al, 1998a(Webb et al, ,b, 2000(Webb et al, , 2001Soufan et al, 2004;Christoffels et al, 2006). Throughout our studies, the key point of our own argumentation has been that, in terms of morphology, the systemic venous sinus cannot be distinguished as a morphologic entity separate from the remainder of the atrial chambers until after the formation of the so-called venous valves (Anderson et al, 2006). In our opinion, Manner and Merkel (2007) fail to give sufficient emphasis to the investigations, already mentioned above, in which we showed that, at the stages before the systemic venous sinus could be distinguished, and before the appearance of the pulmonary vein, the systemic venous tributaries still are embedded in the mesenchyme of the septum transversum, and not yet incorporated into the pericardial cavity (Soufan et al, 2004;Christoffels et al, 2006).…”
supporting
confidence: 63%
“…Moreover, that structures within the right atrium are marked positively for Pitx2 cannot be used as evidence that the developing pulmonary vein was initially in contact with one of the components of the definitive right atrium, namely the systemic venous sinus, as part of normal embryological development. As is shown by molecular studies, the formation of the primary atrial septum, derived from the right pulmonary ridge, composed of mediastinal myocardium, and marked by Pitx2, walls the orifice of the developing pulmonary vein into the morphologically left atrium (Soufan et al, 2004;Mommersteeg et al, 2006). It is not possible that the atrial septum is derived from the morphologically left side, because this would wall the pulmonary veins, surrounded by the mediastinal or mesocardial mesenchyme, into the right atrium (Fig.…”
mentioning
confidence: 97%
“…AP1 proteins regulate a variety of processes including cell proliferation and survival, differentiation, growth, migration, and transformation. Intriguingly, conditional deletion of the AP1 family member Jun using Tie2-Cre leads to DORV, VSDs, and valve defects (54), suggesting that perhaps JUN cooperates with TBX20 in endocardial lineages to effect ture required for proper atrioventricular septation (13,53). Notably, this defect was not observed in our analysis of Nfatc1-Cre Tbx20 fl/fl mutants.…”
Section: Tbx20 Regulates the Endocardial Proliferation And Migratory mentioning
confidence: 82%
“…Notably, this defect was not observed in our analysis of Nfatc1-Cre Tbx20 fl/fl mutants. Unlike the atrioventricular cushions and the mesenchymal cap of the atrial septum, the DMP is not derived from Tie2-Cre lineages (13). Therefore, defects in DMP development in Tie2-Cre Tbx20 fl/null mutants suggest a crosstalk between Tbx20-expressing cells of endocardial lineage and myocardial progenitors of the DMP.…”
Section: Tbx20 Regulates the Endocardial Proliferation And Migratory mentioning
confidence: 99%
See 1 more Smart Citation